Epidemiology and Determine the Causes of Nosocomial Infectioin Teaching Hospital of Tehran: A Cross-Sectional Study - Seyed Mostafa Kohestani; Hojjat Rahmani; Sheyda Nourbakhsh; Farhad Habibi; Ghasem Rajabi Vasoukolaei (Tehran University of Medical Sciences, 2019)
Background: Nosocomial Infections (Nis) Are Regarded As The Most Common Complications Of Health Cares. These Infections Affect Patient's Safety in Developing and Developed Countries. The Aim Of This Study Was To Epidemiology and Determine the Causes of Nosocomial Infectioin Teaching Hospital of Tehran In A Teaching Hospital In Tehran. Materials and Methods: This Cross-Sectional, Descriptive And Analytical Study Was Designed In 2019 At A Teaching Hospital Affiliated With Iran University Of Medical Sciences. The Nosocomial Infection Registry Data between 2017 and 2018 Was Used. The SPSS24.0 Software Package Was Used To Analyze Data Into Descriptive (Frequency, Percentage, Mean and Standard Deviation( And Analytical) ANOVA) Statistics. Result: The Most Frequent Type of Infections Were Urinary Tract (39.76%), Ventilator Associated Events (20.92%), Bloodstream (20.71%), Respectively. Skin and Soft Tissue Infections (0.7%) Had The Lowest Prevalence. The Highest Incidence Of Nosocomial Infection Was In The ICU With 200 Patients And The Lowest Incidence Was In The ENT With 23.1 Patients And The Overall Incidence Of Nosocomial Infections Was 84.9 Patients Per 10,000 Patient-Days. Conclusion: Designing The Related Interventions To Control Nosocomial Infections, Making Hospital Managers And Staff To Sensitive In Nis Control, Holding Specialized Training Programs, Considering Basic Design Of The Physical Structure Of Hospital Wards, Considering Attitudinal And Motivational Are The Most Effective Ways To Combat Nosocomial Infections.